Well-monocrystallized LaCrO3 particles from a LaCrO4 precursor by supercritical hydrothermal technique. Issue 83 (22nd August 2016) - Girish, H.-N.; Shao, G.-Q.; Basavalingu, B.
Abstract : LaCrO3 based materials are currently utilized in a variety of electrical applications at high temperature. Abstract : LaCrO3 based materials are currently utilized in a variety of electrical applications at high temperature. However, the morphology of LaCrO3 powder is much less understood as compared to its bulk counterpart. In this work, LaCrO3 powder was synthesized from LaCrO4 precursor by a supercritical hydrothermal technique (SHT). The majority exhibited a pure orthorhombic phase with well-monocrystallized grains of 3–9 μm. This work confirms that dominating faces in LaCrO3 grains are {0 1 0} and {0 1 1} surfaces, which have equivalent surface-energy due to the similarity of their surface structure.